Prospective observational cohort study on grading the severity of postoperative complications in global surgery research. Issue 2 (8th January 2019) - ,
Abstract : Background: The Clavien–Dindo classification is perhaps the most widely used approach for reporting postoperative complications in clinical trials. This system classifies complication severity by the treatment provided. However, it is unclear whether the Clavien–Dindo system can be used internationally in studies across differing healthcare systems in high‐ (HICs) and low‐ and middle‐income countries (LMICs). Methods: This was a secondary analysis of the International Surgical Outcomes Study (ISOS), a prospective observational cohort study of elective surgery in adults. Data collection occurred over a 7‐day period. Severity of complications was graded using Clavien–Dindo and the simpler ISOS grading (mild, moderate or severe, based on guided investigator judgement). Severity grading was compared using the intraclass correlation coefficient (ICC). Data are presented as frequencies and ICC values (with 95 per cent c.i.). The analysis was stratified by income status of the country, comparing HICs with LMICs. Results: A total of 44 814 patients were recruited from 474 hospitals in 27 countries (19 HICs and 8 LMICs). Some 7508 patients (16·8 per cent) experienced at least one postoperative complication, equivalent to 11 664 complications in total. Using the ISOS classification, 5504 of 11 664 complications (47·2 per cent) were graded as mild, 4244 (36·4 per cent) as moderate and 1916 (16·4 per cent) as severe. Using Clavien–Dindo, 6781 of 11 664 complications (58·1 per cent) were graded as I or II, 1740 (14·9 per cent) as III, 2408 (20·6 per cent) as IV and 735 (6·3 per cent) as V. Agreement between classification systems was poor overall (ICC 0·41, 95 per cent c.i. 0·20 to 0·55), and in LMICs (ICC 0·23, 0·05 to 0·38) and HICs (ICC 0·46, 0·25 to 0·59). Conclusion: Caution is recommended when using a treatment approach to grade complications in global surgery studies, as this may introduce bias unintentionally. Abstract : The Clavien–Dindo classification is perhaps the most widely used approach to reporting postoperative complications in clinical trials. However, it is unclear whether it can be used internationally in studies across differing healthcare systems in high‐ (HIC) and low‐ to middle‐income (LMIC) countries. The results of this study suggest that caution is needed when using treatment approach to grade complications in global surgery studies, as this may unintentionally introduce bias. The challenge of standard measures